DETERMINAN KEPATUHAN WAJIB PAJAK BADAN (Studi Kasus di KPP Pratama Salatiga) - Pancawati Hardiningsih (Dinamika Akuntansi Keuangan dan Perbankan, 2014)
This reserach aims to examine and analyze the effect of perceived behavioral control, financial condition, the condition ofits facilities and the organization climatic conditions on tax compliance manufacturing industry. The population in thisstudy is the Corporate Tax payers manufacturing industry in the territory of Salatiga STO. Sample selection method usedwas convinience sampling. The data analysis technique used is multiple regression linier analysis. Based on the results oftests performed can be found that the perception of behavioral control, financial condition, the condition of its facilitiesand the organization climatic conditions and a significant positive effect on tax compliance entities, either partially orsimultaneouslyKeywords: perceived behavioral control, financial condition, the condition of its facilities, the organizationclimaticconditions and compliance corporate tax payers